Dampak Bisnis Online Shop dan Gaya Hidup terhadap Perilaku Konsumtif Mahasiswa Perbankan Syariah STAI Jam’iyah Mahmudiyah Tanjung Pura - Arziki, Muhammad; Fuadi, Ahmad; Sinaga, Asmawarna (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
The study aims to determine the partial and simultaneous effect of online shop and lifestyle on consumptive behavior of Islamic Banking students at STAI Jam'iyah Mahmudiyah Tanjung Pura. The data source for this research was obtained from questionnaire answers given by research respondents, namely students of the Islamic Banking Study Program, STAI Jam'iyah Mahmudiyah Tanjung Pura, as many as 70 respondents. Data analysis in this study used validity test, reliability test, classical assumption test, hypothesis test, and multiple linear regression analysis. Based on this test, it explains that there is a significant influence both partially and simultaneously between the online shop business and lifestyle on the consumptive behavior of Islamic Banking students at STAI Jam'iyah Mahmudiyah Tanjung Pura. The online shop business and lifestyle influence the consumptive behavior of STAI Jam'iyah Mahmudiyah Tanjung Pura Islamic Banking students by 56.3%, while the rest are influenced by other variables such as pocket money, social status, joining in and others. There is a positive or parallel relationship between the development of the online shop business and lifestyle with consumptive behavior, if the development of the online shop business increases and the lifestyle is high, the consumptive behavior of Islamic Banking students at STAI Jam'iyah Mahmudiyah Tanjung Pura will also increase, and vice versa if the development of the online shop business is decreasing and the lifestyle they have is decreasing, so the consumptive behavior of Islamic Banking students at STAI Jam'iyah Mahmudiyah Tanjung Pura will also decrease.